The Molecular Spectrum of β- and α-Thalassemia Mutations in Non-Endemic Umbria, Central Italy. (1st November 2016) - Gorello, Paolo; Arcioni, Francesco; Palmieri, Antonietta; Barbanera, Ylenia; Ceccuzzi, Laura; Adami, Cecilia; Marchesi, Mauro; Angius, Antonella; Minelli, Olivia; Onorato, Marina; Piga, Antonio; Caniglia, Maurizio; et al.
Abstract: The aim of this study was to describe the mutational spectrum of hemoglobinopathies during the period 1988–2015 in Umbria, Central Italy, which has never been considered endemic for these conditions. Twenty-four different β-globin gene mutations were identified in 188 patients and eight different α-globin gene mutations in 74 patients. Sixty percent β-thalassemia (β-thal), 85.0% sickle cell disease, 44.0% Hb S ( HBB : c.20A>T)/β-thal and 85.0% compound heterozygotes for hemoglobin (Hb) variant-carrying patients were diagnosed or molecularly characterized in the last 3 years. Moreover, most homozygous or compound heterozygous patients (84.5%) came from foreign countries, while only 15.5% were of Italian origin. These data are in accordance with the increasing foreign resident population in Umbria, which has nearly doubled in 10 years (2004–2014). Different from β-globin gene variations, no increasing trend in α defects was observed in our study cohort. Consistently, 58.0% of patients have an Italian origin, suggesting no broad influence of foreign migration in the α-globin genes genetic background. As few defects are prevalent in each country of origin or ethnic group, their knowledge may provide a proper strategy for the identification of mutations in immigrant individuals in a non-endemic region and be important for carrier identification and prenatal screening.